In the picture : preservation and digitisation of European photographic collections - Edwin Klijn, Yola de Lusenet. (European Commission on Preservation and Access, 2000)
Includes bibliographical references (p. [57]-64).The publisher's URL: http://www.knaw.nl/ecpa.